Assessment of procedural parameters recorded following spinal anaesthesia for caesarean section at three academic hospitals in Gauteng - Steynberg, Joubert Casper (My University, 2015)
Currently spinal anaesthesia is widely considered as the safest technique for caesarean section because the increased risk of failed intubation and aspiration associated with pregnant patients is avoided. In South Africa the latest confidential enquiry into maternal mortality for the triennium 2008 – 2010 showed that the maternal mortality rate due to anaesthesia is approximately 5 per 100 000 live births, and the majority (79%) occurred under spinal anaesthesia. This represents a high rate of maternal mortality due to anaesthesia, and particularly spinal anaesthesia, when compared to developed countries. Good anaesthetic records are vital in understanding why the maternal mortality rate due to anaesthesia is so high, and the parameters that are recorded following spinal anaesthesia has not been investigated in South Africa. The primary objectives of this study were to describe the demographics, essential procedural parameters, additional procedural parameters and the clinical parameters recorded following spinal anaesthesia for caesarean section. The secondary objectives of this study were to compare whether surgery being performed during the week or over the weekend, surgery being performed during the day or during the night, surgery being routine or an emergency or the category of anaesthetist influenced the parameters recorded. The research design used in this study was that of a retrospective, contextual, descriptive study. The study population was the anaesthetic records completed following spinal anaesthesia for caesarean section in the maternity theatres of Chris Hani Baragwanath Academic Hospital, Charlotte Maxeke Johannesburg Academic Hospital and Rahima Moosa Mother and Child Hospital. Consecutive convenience sampling was used to select 300 anaesthetic records to be enrolled into the study. Anaesthetic records at each hospital were reviewed from 30 June 2013 backwards until the required sample size for each hospital was reached. Records were enrolled into the study proportionally to the average number of caesarean sections performed at each hospital per month. The majority of records were completed during the week and during the night, most of these anaesthetic records were for emergency surgeries and most were completed by registrars. The study revealed that demographic data and identifying parameters were recorded thoroughly. Eight of the twelve essential procedural parameters were recorded adequately. From the twelve additional procedural parameters identified from the records only two were recorded adequately and from the five clinical parameters reviewed four were recorded acceptably. Records were found to be more comprehensive when completed during the week, when completed during the night, when completed for emergency surgery and when completed by a registrar.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg, 2014